Are we there yet with patent foramen ovale closure for secondary prevention in cryptogenic stroke? A systematic review and meta-analysis of randomized trials. (February 2019) - Agasthi, Pradyumna; Kolla, Kantha Ratnam; Yerasi, Charan; Tullah, Sibghat; Pulivarthi, Venkata Siva; Louka, Boshra; Arsanjani, Reza; Yang, Eric H; Mookadam, Farouk; Fortuin, F David
Background: We performed a meta-analysis to evaluate the benefit of patent foramen ovale closure in stroke prevention. Methods: We searched Medline/PubMed, EMBASE, Web of Science and Cochrane central database for randomized control trials assessing the incidence of recurrent stroke after patent foramen ovale closure when compared to medical therapy. Pooled odds ratio and 95% confidence intervals were calculated using a random effects model. The heterogeneity among studies was tested using the χ 2 test and inconsistency was quantified using the I 2 statistic. Results: Our search strategy yielded 71 articles. We included five studies with a total of 3440 patients. Median age in the device group was 45 (43, 5.5) years and in the medical group was 45 (44.5, 46) years; 52% were male, 27.7% of patients had an atrial septal aneurysm, 25% had hypertension, and 20.5% had diabetes mellitus. The median follow-up time was 44 (34.5–50) months. The pooled odds ratio of recurrent stroke, transient ischemic attack and composite end point of stroke + transient ischemic attack + peripheral embolism in the patent foramen ovale closure versus medical therapy group were 0.4 (95% confidence interval 0.25–0.63, I 2  = 57.5%), 0.93 (95% confidence interval 0.61–1.42, I 2  = 0%), and 0.6 (95% confidence interval 0.44–0.82, I 2  = 0%), respectively. The incidence of atrial fibrillation was found to be significantly higher in the patent foramen ovale closure group with odds ratio of 6 (95% confidence interval 3.13–11.4, I 2  = 33.5%). On subgroup analysis, patent foramen ovale closure appeared to benefit males and patients with a large shunt. Number needed to treat to prevent one recurrent stroke with patent foramen ovale closure is 42. Number needed to harm to cause one atrial fibrillation with patent foramen ovale closure is 39. Conclusion: This meta-analysis of randomized trials concludes that percutaneous patent foramen ovale closure is effective in recurrent stroke prevention especially in males and in those with a large shunt.